Pemantauan Dan Pengelolaan Air Pada Tambang Batubara PT Bukit Makmur Mandiri Utama Kabupaten Berau Provinsi Kalimantan Timur - Sukamto, Purwoto; Widodo , Sri; Nawir , Alfian; Thamsi, Alam Budiman (CV Insight Publisher, 2023)
In the mining industry, especially coal mining of PAF materials which are the source of mine acid formation when interacting with water (H2O) and air (O2) Should be managed as best as possible to minimize acid mine water in the pit before the water is pumped out. This research aimed to determine the method used in handling AAT forming material and to discover whether the quality of wastewater from the settling pond is by wastewater quality standard. The stages and processes of research consist of four steps: data retrieval techniques, data processing, data analysis stages, and the report generation stage. The data taken are primary data, such as inlet and outlet pH and the types of PAF and NAF rock and secondary data, which are company profile data required in report writing. After the data is collected, the data is analyzed to determine the method used in PT. Bukit Makmur Mandiri Utama (BUMA) for AAT handling. In the prevention of the establishment of AAT PT. BUMA applies a capsulization method for handling AAT PT. BUMA has WMP. Water quality with pH parameters at inlet zone 4 and outlet 6, TSS ranged from 6 - 4, Fe <0.02, Mn 2.67 – 2.77. the conclusion of this research is handling the establishment of AAT PT. BUMA performs two ways: the capsulization method and provision of lime neutralizing materials; the water pH in the sediment pond that is four while the pH of water issued is 6, and the amount of lime required is 765,534 kg. Water flowed by PT. BUMA has met the wastewater quality standard set by Kep. Men LH no. 113 the year 2003.